PEMERIKSAAN HIPERTENSI PADA LANSIA DI KOMUNITAS YOGA DHSP BALI, BANJAR SINGIN, SELEMADEG, KABUPATEN TABANAN - I Gede Eka Agung Agastya Punia,; Putu Setiani,; I Putu Pradiva Satriya Kirana,; Kadek Satya Manggala,; Kadek Ayu Wiswapawani, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is one of the most common health problems in the elderly and is the main risk factor for cardiovascular disease, stroke, and kidney failure. This examination aims to detect hypertension in the elderly community at DHSP Bali. The results of blood pressure screening showed that almost half of the participants in the DHSP Bali community were prone to hypertension, namely 15 people (46,87%). Adequate therapy handling, periodic monitoring and prevention education are needed to be able to reduce the number of complications due to hypertension in the elderly group.